Analisis Harga Saham dengan Berdasarkan Rentang Waktu Sebagai Dasar dalam Penentuan Metode Peramalan yang Optimal - Muhammad, Hubbi; Pramesti Melyna Mustofa (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
The modeling of stock prices for telecommunications companies in Indonesia (TBIG.JK, TLKM.JK, XL.JK, ISAT.JK, TOWR.JK) is examined in this study by considering three time periods: 1 year, 5 years, and 10 years. The analysis results indicate that the distribution of stock prices for each company and time period varies, with some stocks exhibiting a distribution close to normal while others show high kurtosis. These findings suggest that the assumption of normal distribution may not be appropriate for all cases, making it essential to select a stock price prediction model that takes into account the specific distribution characteristics for each company and time period